Adaptive sliding mode control with guaranteed performance based on monitoring and barrier functions. (24th May 2021) - Rodrigues, Victor Hugo Pereira; Hsu, Liu; Oliveira, Tiago Roux; Fridman, Leonid
Summary: This paper proposes a new adaptive sliding mode control approach via output feedback for a class of nonlinear systems. The sliding‐mode based controller can deal with parametric uncertainties and (un)matched disturbances with unknown upper bounds. Finite‐time convergence of the tracking error to a predefined neighborhood of the origin of the closed‐loop system is proved with guaranteed transient and steady‐state performance. Basically, the novelty of our result lies on combining two important adaptation tools: monitoring and barrier functions. The adaptation process is divided into two stages, where an appropriate monitoring function allows for the specification of performance criteria during the transient phase, while the barrier function ultimately confines the tracking error within a small residual set in steady state. Simulation results including an application to Anti‐lock Braking System illustrate the advantages of the proposed adaptive control strategy.